Mempertanyakan Stereotip Kecantikan (Analisis Semiotika tentang Representasi Kecantikan dalam Film Adaptasi Snow White and the Huntsman (2012) dan Mirror Mirror (2012)) - Dira Elita (Jurnal Komunikasi)
Fairy tales is a kind of story told orally by our parents from one generation to another. Mainly, the main story is about “beauty”: the princess should be beautiful and the prince should be handsome and know how to fight. When fairy tales such as Snow White adapted into movies, issues related to the concept of beauty is not left behind. This is part of main depiction represented within this kind of film that leads to many stereotypes. This research focuses on how stereotypes of beauty are represented in two fairy tales-based adaptation films, Snow White and the Huntsman (2012) and Mirror mirror (2012). In terms of the methodology, this research employs Roland Barthes’s thought, especially his structural semiotic analysis. By applying Barthes’s “two orders of signification” (denotation and connotation), the analysis focuses on three thematic elements: body, costume, and characteristic.